KNOWLEDGE OF THE APPROACHES TOWARDS CANCER PAIN MANAGEMENT IN PATIENTS CARE AMONG NURSES IN SELECTED HOSPITALS IN AKWA IBOM STATE (Journal of Biomedical Investigation, 2023)
Background: Cancer-related pain can be acute or chronic and related to tumour, treatment, or both. Cancer pain has a debilitating effect and, if left untreated or poorly managed, can have a significant impact on a patient's physical, emotional, and mental well-being, thus impairing the patient's quality of life. Immediately a comprehensive assessment of a patient's pain is concluded, different treatment approaches should be considered before treatment planning is developed.Aim: This study examined knowledge and approaches used in managing cancer pain in cancer patients among nurses in selected hospitals in Akwa Ibom State, Nigeria.Materials and methods: A cross-sectional descriptive survey was carried out among 88 registered nurses purposely recruited from selected hospitals in Akwa Ibom State. Data was collected using Observational checklist and revised Nurses Knowledge and Attitudes Survey Regarding Pain (NKASRP) questionnaire. The obtained data were summarized using frequencies, Percentages and chi-square.Results: More than half of the nurses 64 (73.70%) had adequate knowledge about cancer pain management while only 3 out of 10 cancer pain management approach was satisfactorily utilized by the participants in the care of cancer patient aimed at relieving pain.Conclusions: Although more of the nurses had adequate knowledge on cancer pain management, the approach used was sub-optimal.
Keywords: cancer pain; management approach; nurses